A Retrospective Cohort Study of Healthcare Utilization Associated with Paravertebral Blocks for Chronic Pain Management in Ontario. Issue 1 (1st January 2021) - Deng, George; Gofeld, Michael; Reid, Jennifer N; Welk, Blayne; Agur, Anne MR; Loh, Eldon
ABSTRACT: Background : Injections, particularly paravertebral blocks (PVBs), are frequently performed procedures in Ontario, Canada, for the management of chronic pain, despite limited evidence and risk of complications. Aim: This study examines usage patterns of PVBs to evaluate their effects on healthcare utilization and opioid prescribing. Methods: A retrospective cohort study in Ontario using administrative data. Ontario residents receiving their initial PVBs between July 1, 2013 and March 31, 2018 were included. Changes in use of other interventions, physician visits, and opioids were compared to the 12-month periods before and after index PVBs. Data use was authorized under section 45 of Ontario's Personal Health Information Protection Act. Results: 47, 723 patients received their initial PVBs in the study period. The rate of index PVBs increased from 1.61 per 10, 000 population (2013) to 2.26 per 10, 000 (2018). Initial PVBs were performed most commonly by family physicians ( N = 25, 042), followed by anesthesiologists ( N = 14, 195). 23, 386 patients (49%) received 1 to 9 repeat PVBs in the 12 months after index PVB; 12, 474 patients (26.15%) received 10 or more. Use of other nonimage guided interventional pain procedures per patient (mean±SD) increased from 2.19 ± 9.35 to 31.68 ± 52.26 in the year before and after index PVB. Relevant physician visits per patient (mean±SD) also increased from 2.92 ± 3.61 to 9.64 ± 11.77. Mean opioid dosing did not change significantly between the year before and the year after index PVB. Conclusion: PVBs are associated with increases in healthcare utilization and no change in opioid use patterns.